Carbon Isotope Discrimination as an Indicator of Vine Water Status is Comparable in Grape Must, Wine, and Distilled Wine Spirits - Gowdy, Mark; Julliard, Sébastien; Frouin, Marina; Poitou, Xavier; Destrac Irvine, Agnès; van Leeuwen, Cornelis (Frontiers in Food Science and Technology, 2022)
Measurement of carbon isotope discrimination (δ13C) in berry juice sugars provides an integrative indicator of grapevine water status during berry ripening. Characterizing vine water status during this critical period is useful because it has an important effect on the quality of grapes and the resulting wine. The δ13C of the sugar in grapes is also strongly correlated to the δ13C of the ethanol that results when they are fermented into wine. This then provides a means of estimating from a sample of wine the vine water status that existed during the corresponding berry ripening period, and can be used to establish relations between vine water status and specific sensory attributes of wine quality. The same would be possible for evaluating the sensory attributes of wine spirit (eau de vie) if it was understood how the δ13C signal was affected by the distillation process. In this study, the δ13C in eau de vie, produced by a double distillation process similar to that used in the Cognac region of France, was measured and compared to its source wine and parent grape must. A strong relationship was found between the δ13C of grape must and subsequent wine and eau de vie, suggesting the latter can indeed be used to estimate the vine water status that existed during the corresponding berry ripening period. In this way, future studies of sensory attributes of eau de vie can be linked to vine water status during berry ripening, such as has been done previously for wine.